Adsorption kinetics and dilatational rheological properties of recombinant Pea Albumin-2 at the oil-water interface. (November 2021) - Luo, Yilun; Zheng, Wei; Shen, Qian; Zhang, Li; Tang, Cuie; Song, Rong; Liu, Shilin; Li, Bin; Chen, Yijie
Abstract: To investigate the adsorption kinetics and dilatational rheological properties of Pea Albumin-2 (PA-2) at the oil-water interface, recombinant PA-2 was expressed and purified. Our native-PAGE, SDS-PAGE, and homology modeling results indicated that PA-2, a kind of globular protein, could form dimers by non-covalent interactions rather than disulfide bonds. The TEM results showed that some PA-2 proteins could form aggregates with the size of around 2–3 μm. Unlike other globular proteins, PA-2 exhibited the non-monotonic kinetic dependency of the dynamic viscoelastic modulus (E). Besides, the rate of rearrangement ( k R ) of PA-2 was significantly higher than that of other typical food proteins. Our results demonstrated that PA-2 could adsorb to the oil-water interface in the form of aggregates. The addition of 2-ME (β-mercaptoethanol) would impact dilatational rheological properties of PA-2, leading to disaggregation and higher rearrangement of PA-2 protein aggregates at the oil-water interface. Our data offered more information on the interfacial dynamic properties of globular proteins, and provided a new insight to the conformational changes of globular proteins at the oil-water interface, basing on their dynamic viscoelastic behaviors. Graphical abstract: Image 1 Highlights: PA-2 could adsorb to the oil-water interface in the form of aggregations. PA-2 exhibits a non-monotonic kinetic dependency of the viscoelastic modulus (E). PA-2 with β-mercaptoethanol treatment exhibits higher conformational flexibility. The increasing conformational flexibility improves the interfacial rearrangement. The high viscoelastic modulus (E) is mainly provided by rigid globular monomer.